A synchronous virtual surgical lecture series on cardiothoracic, vascular, oncology, and transplant surgery for surgical trainees in Sub-Saharan Africa: the COSECSA learner perspectives - Abebe Bekele; Oluwaseun Ojomo; Jules Iradukunda; Niraj Bachheta; Callum Forbes; Pierrette Ngutete Mukundwa; Victor Mithi; Michael Mwachiro; Robert Riviello; Dereje Gulilat; Stella Itungu; Barnabas Tobi Alayande (BMC Medical Education)
Abstract Introduction The College of Surgeons of East, Central, and Southern Africa (COSECSA) training program requires completion of a mandatory rotation in vascular and cardiothoracic surgery. However, few accredited training sites offer such services regularly, hence exposure of trainees to these disciplines is limited. This study evaluates the demand, feasibility, and acceptance of an open-access, synchronous virtual surgical education series to bridge gaps in training. Methods The Center for Equity in Global Surgery at the University of Global Health Equity partnered with COSECSA to develop and deliver interactive sessions on common cardiothoracic, vascular, and transplant surgical topics facilitated by faculty from the COSECSA region and global partner institutions. All sessions were delivered via a cloud-based video conferencing service and recorded for retrospective viewing. At the end of the lecture series, trainees participated in a post-course evaluation survey. Results In total, 2,015 participants from 48 countries attended the lecture series with 977 participants in 2022 and 1,038 in 2023. In 2023, most participants were from Ethiopia (10.9%), Kenya (23.6%), and Uganda (15.4%). Two hundred and fifty-two participants contributed to the post-course evaluation survey, of which only 23% were female and 48% were general surgery trainees. Mean satisfaction with the lecture series on a 5-point Likert scale was 4.5. Participants reported an average satisfaction level of 4.4 for logistics of the series (registration process, ease of connectivity, and time management), 4.5 for content, 4.4 for in-class interactions, 4.4 for use of case-based images, and 4.2 for post-session availability of lecture material. Almost all suggested additional lectures in thoracic infection, vascular trauma, and plastic surgery to be included in subsequent lecture series. Conclusion The study has shown that such an online, synchronous, virtual teaching series is in high demand, feasible, and crucial for closing knowledge gaps in didactic cardiothoracic, vascular, and transplant surgery within the COSECSA region. These sessions are well received by COSECSA trainees and are accessible, highlighting a clear demonstrable need. It is recommended that such efforts be sustained and expanded, with additional competency areas to broaden the impact.